Comparison of active learning models in schools in increasing the cognitive value of students - Tulus; Zarlis, Muhammad; Sawaluddin; Syahputra, M.R. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The term learning model is distinguished from the term learning strategy, method learning or learning procedure. The term learning model has broader meaning than a strategy, approach, method or procedure. Learning models are patterns of interaction between students, teachers, and material learning that includes strategies, approaches, methods and techniques learning. Elaborate that learning strategies are tactics or tips planned by the teacher related to the whole preparation of learning can be achieved effectively. While the approach is the way taken by the teacher in the implementation of learning so that the active ideas presented can be adapted to then be understood by students. There are two types of active learning, namely: a methodological approach and material approach. Methodological approach concerns the way students Adapting the active ideas presented into their cognitive structures that are in line in the way taken by the teacher in presenting learning materials the. Examples of methodological approaches are intuitive, analytic, synthetic, spiral, inductive, deductive, thematic, realistic and heuristic. The result of this research is the material approach able to present an active concept through other active concepts already owned by students. The example presents the concept of addition with using the number line or set approach.